Risk of colorectal cancer associated with BRCA1 and/or BRCA2 mutation carriers: systematic review and meta-analysis. Issue 8 (16th April 2020) - Cullinane, C M; Creavin, B; O'Connell, E P; Kelly, L; O'Sullivan, M J; Corrigan, M A; Redmond, H P
Abstract: Background: Carriers of the BRCA1 and/or BRCA2 mutation incur a lifetime risk of up to 85 per cent for breast cancer, and between 20 and 40 per cent for ovarian cancer. Efforts to estimate the lifetime risk of developing colorectal cancer for BRCA mutation carriers have produced conflicting results. Consequently, there are no formal guidelines regarding the need for bowel screening for individuals with BRCA1 and/or BRCA2 mutations. This systematic review and meta-analysis determined the risk of colorectal cancer associated with BRCA carrier mutations. Methods: The primary outcome was incidence of colorectal cancer in BRCA mutation carriers. Secondary outcomes were the incidence in BRCA1 and BRCA2 carriers, Ashkenazi Jews, and age- and sex-matched cohorts. Results: Eleven studies were included in the review, with an overall population of 14 252 and 4831 colorectal cancers identified. Nine studies were included in the meta-analysis. There was no increase in colorectal cancer among patients carrying a BRCA mutation (odds ratio 1·03, 95 per cent c.i. 0·80 to 1·32; P = 0·82). After adjustment for Ashkenazi heritage, and age and sex estimates, there was no increased odds of developing colorectal cancer (with no heterogeneity, I 2 = 0 per cent). Conclusion: BRCA1 and/or BRCA2 mutation carriers are not at a higher risk of colorectal cancer. Graphical Abstract: BRCA1 and/or BRCA2 mutation carriers incur a lifetime risk of up to 85 per cent for breast cancer, and between 20 and 40 per cent for ovarian cancer. The aim of this study was to clarify whether an association between BRCA mutation and colorectal cancer risk exists by conducting a systematic review and meta-analysis of published peer-reviewed studies. There was no significant increase in the odds of having colorectal cancer in patients carrying a BRCA mutation (odds ratio 1·03, 95 per cent c.i. 0·80 to 1·32; P = 0·82). No increased risk